2015
DOI: 10.1111/ctr.12637
|View full text |Cite
|
Sign up to set email alerts
|

Filgrastim versus TBO‐filgrastim to reduce the duration of neutropenia after autologous hematopoietic stem cell transplantation: TBO, or not TBO, that is the question

Abstract: After a hospital-wide formulary change resulted in the replacement of filgrastim with TBO-filgrastim for all on- and off-label indications, we performed a retrospective comparison of patients with myeloma receiving 200 mg/m(2) melphalan with autologous hematopoietic stem cell transplantation to see whether the type of growth factor used post-transplant made a difference. One hundred and eighty-two consecutive patients with myeloma were studied, 91 receiving filgrastim immediately prior to the change and 91 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A 1‐day difference in engraftment was observed between treatment groups. TBO‐filgrastim, used during the levofloxacin treatment period, has been shown to delay engraftment compared to filgrastim, without compromising clinical outcomes or duration of hospital admission …”
Section: Discussionmentioning
confidence: 99%
“…A 1‐day difference in engraftment was observed between treatment groups. TBO‐filgrastim, used during the levofloxacin treatment period, has been shown to delay engraftment compared to filgrastim, without compromising clinical outcomes or duration of hospital admission …”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences noted between any of the engraftment endpoints, demonstrating equivalence between the two products in supporting stem cell engraftment as shown in other retrospective observations. 11,12,15 In comparison to a retrospective review published in 2015 that showed significantly less documented infections in patients using tbo-filgrastim versus filgrastim for stem cell mobilization and engraftment, there was no difference in the number of infections documented per patient during this study. However, the filgrastim group had a larger number of positive blood cultures, gram positive bacterial cultures, and a larger number of documented clostridium difficile infections, while the tbo-filgrastim cohort had a larger number of confirmed respiratory infections and fungal infections.…”
Section: Discussionmentioning
confidence: 49%
“…This formulary change was based on the use of tbo-filgrastim as a biosimilar in the EU, a group of retrospective evidence demonstrating the safety and efficacy of tbo-filgrastim versus placebo and/or filgrastim, and the potential for significant cost savings by utilizing tbo-filgrastim. [11][12][13][14][15] This study compares the efficacy of tbo-filgrastim versus filgrastim for stem cell mobilization and stem cell engraftment in autologous HSCT recipients along with a financial analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a growing body of evidence on the efficacy and safety of tbo-filgrastim in its off-label indications. 14,19,20 In 1 retrospective study conducted in a U.S. hospital among 185 patients diagnosed with lymphoma or plasma cell disorders undergoing G-CSF mobilization, there was no significant difference seen between filgrastim and tbo-filgrastim in the total collection of CD34(+) cells, which was the primary end point. Furthermore, no clinically meaningful differences were seen in secondary efficacy and safety end points.…”
Section: ■■ Discussionmentioning
confidence: 99%